2019
DOI: 10.1186/s13731-019-0106-y
|View full text |Cite
|
Sign up to set email alerts
|

Does intellectual capital affect the venture creation decision in India?

Abstract: Purpose: Although the intellectual capital (IC) has already received much attention from the researchers in the field of innovation performance, there is still a paucity in measuring the role of IC in venture creation. The present study is an attempt to examine the influence of IC on start-ups. Methodology: In this study, a large data set of 3413 respondents from India has been used. The data has been provided by the largest entrepreneurship research project GEM. A logistic regression technique has been applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 85 publications
3
12
0
Order By: Relevance
“…These learning opportunities are important because communities with a wider network of peers tend to enjoy higher levels of entrepreneurship and economic growth. These results are in agreement with Khan, Arafat, Raushan, Saleem, Khan, Khan and Entrepreneurship [34], who found that networking services can help entrepreneurs attract more customers, knowledge and ultimately achieve business growth and increase profits.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These learning opportunities are important because communities with a wider network of peers tend to enjoy higher levels of entrepreneurship and economic growth. These results are in agreement with Khan, Arafat, Raushan, Saleem, Khan, Khan and Entrepreneurship [34], who found that networking services can help entrepreneurs attract more customers, knowledge and ultimately achieve business growth and increase profits.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study illustrate that networking services have a positive effect on entrepreneurship development. The results related to hypothesis involve coefficient beta 0.237, standard error 0.04, t-value 6.043 > 2, and p-value 0.000 < 0.05, supported by the previous study [34]. Mahmood, Jamil and Yasir [17] found similar results in which involvement in networking activities is an essential role for business incubators because it links entrepreneurs in and out of business incubation with key investors in the community.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…If entrepreneurship is defined as the ability to seize new opportunities (Kirzner, 1973), it becomes important to understand if and how the set of internal and external knowledge of a subject can facilitate the recognition of a profitable advantage (Ramos-Rodriguez et al, 2010;Khan et al, 2019).…”
Section: Literature Review 21 Entrepreneurship and Icmentioning
confidence: 99%
“…Therefore, governmental institutions should encourage systems of human and structural capital development, so as to encourage the exchange of knowledge and skills necessary for business creation (Khan et al, 2019). IC is the substrate of any business model, in which a central role is played by the person, as such and as a member of a group, who cooperates for the sharing of knowledge at every corporate level, promoting the creation of value (Nielsen and Dane-Nielsen, 2019).…”
Section: Literature Review 21 Entrepreneurship and Icmentioning
confidence: 99%